2012
DOI: 10.1128/mcb.06769-11
|View full text |Cite
|
Sign up to set email alerts
|

A WNT/p21 Circuit Directed by the C-Clamp, a Sequence-Specific DNA Binding Domain in TCFs

Abstract: The lymphoid enhancer factor 1/T cell factor (LEF/TCF) family of transcription factors are downstream effectors of the WNT signaling pathway, which drives colon tumorigenesis. LEF/TCFs have a DNA sequence-specific high-mobility group (HMG) box that binds Wnt response elements (WREs). The "E tail" isoforms of TCFs are alternatively spliced to include a second DNA binding domain called the C-clamp. We show that induction of a dominant negative C-clamp version of TCF1 (dnTCF1E) induces p21 expression and a stall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(90 citation statements)
references
References 76 publications
9
79
2
Order By: Relevance
“…The present study showed that the expression of Sp5 is not upregulated in HCT116 cells, in which Wnt signaling is constitutively activated. Although other studies have reported that Sp5 represses the expression of p21 and promotes the growth of MCF-7 cells (11,14,17), no significant changes could be detected in the p21 expression in the HCT116 cells transfected with Sp5 in the present study. This discrepancy may be due to the differences in cell types and the different expression levels of the Sp family of proteins.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…The present study showed that the expression of Sp5 is not upregulated in HCT116 cells, in which Wnt signaling is constitutively activated. Although other studies have reported that Sp5 represses the expression of p21 and promotes the growth of MCF-7 cells (11,14,17), no significant changes could be detected in the p21 expression in the HCT116 cells transfected with Sp5 in the present study. This discrepancy may be due to the differences in cell types and the different expression levels of the Sp family of proteins.…”
Section: Discussioncontrasting
confidence: 50%
“…It has been reported that overexpression of Sp5 suppresses p21 expression (11,14,17). However, in the present study, RT-qPCR analysis revealed that overexpression of mSp5 did not affect the expression levels of p21 in HCT116 cells (Fig.…”
Section: A B C D Econtrasting
confidence: 50%
See 1 more Smart Citation
“…The full-length human HNF4␣2 (NM_000457) and HNF4␣8 (NM_175914) cDNAs in pcDNA3.1 were gifts from Christophe Rachez at Pasteur Institute, Paris, France (14,46). The human ApoB.-85.-47.E4.Luc luciferase reporter construct and Flag-dnTCF1E1 (Flag.dnTCF1) and Flag-TCF4E2 (Flag.TCF4) expression vectors have been described previously (29,47).…”
Section: Methodsmentioning
confidence: 99%
“…The targets and gene programs that are misregulated in these cells are specified by the DNA binding specificities of the LEF/TCFs. The factor studied here, TCF1E, contains two DNA binding domains, a WRE binding domain and a C-clamp binding domain [77].…”
Section: Alternative Target Recognition In the Wnt Signaling Pathway mentioning
confidence: 99%